Global temperature behavior monitoring and analysis of a three-tower cable-stayed bridge - Lingfang Li; Yushi Shan; Qiang Jing; Yu Yan; Zili Xia; Yong Xia (Engineering Structures, 2023)

Altered brain activity in the bilateral frontal cortices and neural correlation with cognitive impairment in schizophrenia - Lingfang Yu; Lei Guo; Xinyu Fang; Fuyin Yang; Yan Chen; Yewei Wang; Dandan Wang; Zenan Wu; Ruimei Liu; Xing Tian; Chen Zhang (Brain Imaging and Behavior, 2022)

Analysis and mapping quantitative trait loci for histidine content in barley (Hordeum vulgare L.) using microsatellite markers - Lingfang Yan; Xiaomeng Yang; Zhenghai Sun; Juan Du; Xiaoying Pu; Jiazhen Yang; Yawen Zeng (Genetic Resources and Crop Evolution, 2021)
Mining the gene of histidine content in barley grain helps with the breeding of functional barley varieties. The study constructed a recombinant inbred lines (RILs) containing 193 families derived from the cross between Ziguangmangluoerling (ZGMLEL) (♀) and Schooner No.3 (♂). The histidine (HIS) content in the grain of the mapping population and its parents were determined by an automatic amino acid analyzer. The HIS content of ZGMLEL was 0.53 mg/g. The grain HIS content of Schooner No. 3 was 0.21 mg/g, and the grain HIS content of population ranged from 0.23 to 0.54. Genetic linkage maps, including those of seven chromosomes of barley, were constructed by using 180 pairs of simple sequence repeat (SSR) markers, with a total genetic distance of 2671.03 cM and average marker spacing of 14.84 cM. Quantitative trait locus (QTL) IciMappingV3.3 was used to analyze QTL of HIS content in barley grains, and three QTLs were detected. Mapping results showed that the three loci were located on chromosomes 2H, 4H, and 7H, respectively. The major QTL with a contribution rate of 10.11% was located on barley chromosome 4H (HVBAMMGB84-BMAG0808). The additive effect is positive (0.025). Thus, it comes from the high-value parent ZGMLEL. Another major QTL with a contribution rate of 13.75% was located on barley chromosome 7H (GBM1303-GMS056). The minor QTL with a contribution rate of 6.01% was located on chromosome 2H (Scssr03381-Scssr07759). The additive effects of 4H and 7H QTLs were negative (− 0.02 and − 0.033). So, they came from the male parent Schooner. The results provided a reference for further fine mapping, cloning, and transformation of HIS genes in barley grains.